THE THEME OF THE OCCUPIED MOTHERLAND IN THE WORKS OF MAHMUD DERVISH - Ismailova Yulduz (Journals Park Publishing, 2023)
This article is devoted to the work of one of the most prominent representatives of the Palestinian literature of the twentieth century, Mahmoud Darvish, whose whole life is a confirmation of serving the ideals of the liberation of the occupied lands of Palestine. The analysis involved a number of poems devoted to this topic, in which the active civil position of the poet, his individuality is clearly traced.
Keywords: Palestine, Palestinian literature, the 20th century, Mahmoud Dervish, creativity, the homeland, citizenship, visual means, symbolism.